SYNTHESIS OF 1,2 DISUBSTITUTED BENZO 1,3-DIAZOLE DERIVATIVES AND EVALUATION OF THEIR INVITRO ANTI-TUBERCULAR ACTIVITIES - Prakash, Sunbee; Jat, Dr. Rakesh Kumar (Journal of Biomedical and Pharmaceutical Research, 2019)
The present research work was aimed to synthesize some Mannich bases of benzo1,3-diazole dervivatives and was investigated for their biological activities. The newly synthesized compounds have been characterized by their analytical and spectral (IR, 1HNMR, Mass spectra) properties. All the compounds have been screened for their antitubercular activities by standard methods. Antitubercular study revealed that Both BZ2 and BZ5 have promising activity. Keywords: Benzo1,3-diazole, o-phenylenediamine, urea, benzamide, Hydroxylamine, Antitubercular activity.